Fast chlorophyll a fluorescence induction (OJIP) phenotyping of Arabidopsis single and higher order mutants depleted of proteins involved in donor and acceptor side function of photosystem II - Barbato, Roberto (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025 The Authors. Published by Elsevier Masson SAS.. All rights reserved.